Hak Asasi Manusia dalam Hukum Tata Negara: Antara Teori dan Praktik - syarifudin, udin (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
This research aims to analyze the interaction between human rights and constitutional law in Indonesia, focusing on the discrepancies between theoretical frameworks and practical implementation. To achieve this objective, a qualitative approach was employed, utilizing a literature review and in-depth interviews with legal practitioners and human rights activists. Through this method, the study explores the views and experiences of informants regarding the challenges faced in the enforcement of human rights in the field. The findings indicate that although the Indonesian Constitution fundamentally regulates human rights, the enforcement of these rights often encounters various obstacles. Socio-political factors, such as instability and the attitudes of law enforcement officials, as well as inadequate legal mechanisms, pose significant barriers to the implementation of human rights protection. Additionally, institutional weaknesses within responsible agencies further exacerbate this situation. Therefore, the study concludes that there is an urgent need for reforms in both the legal framework and institutional practices to bridge the gap between theory and reality in the protection of human rights in Indonesia. Consequently, the findings of this research are expected to contribute to the development of policies and efforts for more effective human rights protection in the future.